Remnant cholesterol predicts the development of type 2 diabetes in patients with nonalcoholic fatty liver disease - Liping Yang; Hangkai Huang; Zejun Wang; Chengfu Xu (Diabetology & Metabolic Syndrome)
Abstract Background The predictive value of serum remnant cholesterol in cardiovascular disease has been widely recognized. This value has also been explored in metabolic disorders such as type 2 diabetes mellitus and nonalcoholic fatty liver disease (NAFLD). However, whether remnant cholesterol can predict the risk of incident diabetes in NAFLD patients remains unclear. Methods This study included adults who underwent health examinations from 2004 to 2015. NAFLD was diagnosed via abdominal ultrasonography with the exclusion of other causes of chronic liver disease. Cox proportional hazards regression analyses were performed to investigate the associations between baseline remnant cholesterol and diabetes risk in NAFLD patients and NAFLD-free participants. Results A total of 15,464 participants were included in this study, and 2,741 adults had NAFLD. During the 93,537 person-years of follow-up, 233 cases and 150 cases of incident diabetes were recorded among NAFLD patients and NAFLD-free individuals, respectively. Compared with the first quartile, the fourth quartile of remnant cholesterol was positively associated with the risk of diabetes in NAFLD patients (HR: 1.68, 95% CI: 1.13 − 2.51; P < 0.001). However, this association was not significant in NAFLD-free individuals. Conclusions High remnant cholesterol was associated with an increased risk of incident diabetes in NAFLD patients but not in NAFLD-free individuals.